Design and Simulation of an Analog Robust Control for a Realistic Buck Converter Model - Mohammed, Ibrahim Khalaf; Khalaf, Laith Abduljabbar (Universitas Muhammadiyah Yogyakarta, 2024)
The simplicity and cost of the control systems used in power converters are an urgent aspect. In this research, a simple and low cost voltage regulation system for a Buck converter system operating in uncertain conditions is provided. Using an electronic PID controller technique, the feedback control scheme of the presented Buck converter is carried out. Matlab software used a simulation environment for the proposed analog PID-based Buck converter scheme. The PID controller is easily implementable since it is built with basic and conventional electronic components like a resistor, capacitor and op-amp. The system simulation has high reliability as it is implemented using the Simscape package. The Simscape components used to build the converter system are modeled effectively taking into consideration including the practical factors such as internal resistance, tolerance and parasitic elements. This procedure certainly enhances the reliability of the simulation findings as the working conditions of the simulated system become more closer to the real-world conditions. Particle Swarm Optimization (PSO) is employed to properly optimize tune the PID gains. The regulation process of the PID control scheme is assessed under voltage and load disturbances in order to explore the robustness of the Buck converter performance. The findings from the system simulation, under the uncertainties, show largest rise time and settling time of 20 ms and 25 ms respectively, zero overshoot and minimum steady state error response, except at load disturbance case there is a fluctuation of 1 V. Consequently, It can be said that the proposed Buck converter based on analog PID controller can be used efficiently in the industrial and power applications.